Dual Tasking for the Differentiation between Depression and Mild Cognitive Impairment - Metzger, Florian G.; Hobert, Markus A.; Ehlis, Ann-Christine; Hasmann, Sandra E.; Hahn, Tim; Eschweiler, Gerhard W.; Berg, Daniela; Fallgatter, Andreas J.; Maetzler, Walter; , the TREND Study team (Frontiers in Aging Neuroscience, 2016)
Introduction: Differentiation of mild cognitive impairment from depression in elderly adults is a clinically relevant issue which is not sufficiently solved. Gait and dual task (DT) parameters may have the potential to complement current diagnostic work-up, as both dementia and depression are associated with changes of gait and DT parameters. Methods: Seven hundred and four participants of the TREND study (Tübinger evaluation of Risk factors for Early detection of NeuroDegeneration) aged 50 to 80 years were assessed using the Consortium to Establish a Registry for Alzheimer's Disease Plus test battery for testing cognition and Beck’s Depression Inventory for evaluation of depression. Based on these results, four groups were defined: acute depressed (N=53), cognitively mildly impaired (N=97), acute depressed and cognitively mildly impaired (N=15), and controls (N=536). Participants underwent a 20 m walk and checking boxes task under single (ST) and DT conditions. ST and DT performance and dual task costs (DTC) were calculated. Due to the typical age of increasing incidence of depressive and also cognitive symptoms, the seventh decade was calculated separately. Results: ST speeds of gait and checking boxes, DT walking speed and walking DTC were significantly different between groups. Healthy controls were the fastest in all paradigms and cognitively mildly impaired had higher DTC than depressed individuals. Additionally, we constructed a multivariate predictive model differentiating the groups on a single-subject level. Conclusion: DT parameters are simply and comfortably measureable, and DTC can easily be determined. The combination of these parameters allows a differentiation of depressed and cognitively mildly impaired elderly adults.